Understanding individual differences in theory of mind via representation of minds, not mental states - Conway, J; Catmur, C; Bird, G (Springer US, 2019)
The human ability to make inferences about the minds of conspecifics is remarkable. The majority of work in this area focuses on mental state representation (‘theory of mind’), but has had limited success in explaining individual differences in this ability, and is characterized by the lack of a theoretical framework that can account for the effect of variability in the population of minds to which individuals are exposed. We draw analogies between faces and minds as complex social stimuli, and suggest that theoretical and empirical progress on understanding the mechanisms underlying mind representation can be achieved by adopting a ‘Mind-space’ framework; that minds, like faces, are represented within a multidimensional psychological space. This Mind-space framework can accommodate the representation of whole cognitive systems, and may help to explain individual differences in the consistency and accuracy with which the mental states of others are inferred. Mind-space may also have relevance for understanding human development, intergroup relations, and the atypical social cognition seen in several clinical conditions.